THE USE OF KAHOOT AS TEACHING MEDIA, IN TEACHINGVOCABULARY FOR GRADE EIGHT STUDENTS SMP PGRI 1 SEMARANG IN ACADEMIC YEAR 2023/2024 - Widiasih, Karina; Affini, Laily Nur; Sophia B, Th. Cicik (Universitas Muria Kudus, 2024)
In learning English, students are expected to master four essential skills, with each student typically needing to focus on improving their weakest area among these four. These skills encompass various sub-components, notably grammar and vocabulary. This research specifically targets vocabulary acquisition, acknowledging the unique challenges it presents in the learning journey. The study employs Kahoot as the primary instructional tool, as it closely aligns with modern educational practices. Some students lack proficiency in English and have never formally studied vocabulary. Consequently, this study aims to assess the effectiveness of Kahoot in enhancing students' vocabulary skills. The study involves 30 eighth-grade students and utilizes descriptive qualitative methods for data collection, which include observation, administering questionnaires, and conducting interviews. The findings indicate a positive impact of Kahoot on the learning process, particularly in vocabulary acquisition. Most students express agreement regarding the utility of using Kahoot as an alternative method to enhance their English learning, especially in the realm of vocabulary.